En grafisk trestegsraket : En studie om att utifrån tre olika spelsätt tolka ett grafiskt noterat stycke för soloklarinett - Roos, Mikael (2016)
The aim of this work is to explore how I can use three different playing techniques on the clarinet in my interpretation of the Trinity, a graphic scored piece composed by Kristin Boussard.In this project, I have interpreted Trinity, a graphic scored piece for solo clarinet composed by Kristin Boussard. The piece consists of three movements, and for each movement, I have used a chosen playing technique. The three different playing techniques I have used are: traditional sounding tones, alternate playing techniques that do not generate traditional sounding tones and finally traditional sounding tones combined with three electronic pedal effects, distortion, delay and chorus effects. I have made profound analysis of the graphic score based on a variety of musical aspects. Afterwards I have made a practical interpretation of the piece which has generated additional analyzes and reflections on the relationship between the graphical notation and the sounding result.My result shows the different ways that I, as a clarinetist, can work with a crafted graphic piece. I show the different approaches in my analysis and what the graphic score tells me without having any, in advance, given guidelines.The artistic part of this project consists of a recording of the Trinity, made February 29th 2016 in the auditorium of the School of Music in Piteå. Validerat; 20160626 (global_studentproject_submitter)